Treatment of the Obese Patient - Kushner, Robert F.; Kushner, Robert F.; Bessesen, Daniel H.; Bessesen, Daniel H. (Contemporary Endocrinology,, 2007)
The aim of Treatment of the Obese Patient is to inform clinicians of recent advances in obesity research and provide an up-to-date review of current treatment issues and strategies. Divided into two sections, the first section covers new discoveries in the physiological control of body weight, as well as the pathophysiology of obesity. The second section covers a range of issues that are central to the clinical management of obese patient. This volume is a resource that will stimulate and engage clinicians to take part more successfully in the obesity-care process.